Prevalence and pattern of PCOS in women presenting with acne, a hospital based prospective observational study - Shareef A., Raja; Prasad, P. V. S.; Kaviarasan, P. K. (International Journal of Research in Medical Sciences, 2018)
Background: Acne is one of the most common dermatological conditions encountered in day to day practice. Many recent studies have reported a strong association between acne and underlying systemic endocrine disorders, more particularly Poly cystic ovarian syndrome. But there is scarcity of literature on the subjects in Indian population. Hence the present study was conducted with an objective of studying the association between acne and polycystic ovarian syndrome, in women presenting with adult onset acne to a tertiary care teaching hospital. Methods: A prospective observational study was carried out in department of dermatology, Dhananalakshmi Srinivasan medical college and hospital, Permabalur from January 2016 to August 2017. The study population included women above 18 years of age clinically diagnosed with acne vulgaris. The presence of polycystic ovarian syndrome was assessed using Rotterdam criteria. Results: The final analysis had included 100 women with acne. The most common type of lesion observed was comedone in 91% of women. The other most common lesions were papule seen in 73%, pustule in 35% of women. The proportion with grade I, Grade II and grade III acne was 58%, 29% and 13% respectively. The prevalence of PCOS was 30% (95% CI 21.89% to 39.58%). PCOS had shown no statistically significant association with age, marital status and regularity of menstrual cycle. The factors which have shown statistically significant association were higher BMI, presence of Hirsutism and higher waist circumference. Conclusions: PCOS is highly prevalent among women with acne. Presence of hirsutism, obesity are strong risk factors for PCOS.